Population structure and associated phenotypes of Salmonella enterica serovars Derby and Mbandaka overlap with host range - Hayward, Matthew R. (BMC Microbiol, 2016)
BACKGROUND: The Salmonella enterica serovar Derby is frequently isolated from pigs and turkeys whereas serovar Mbandaka is frequently isolated from cattle, chickens and animal feed in the UK. Through comparative genomics, phenomics and mutant construction we previously suggested possible mechanistic reasons why these serovars demonstrate apparently distinct host ranges. Here, we investigate the genetic and phenotypic diversity of these two serovars in the UK. We produce a phylogenetic reconstruction and perform several biochemical assays on isolates of S. Derby and S. Mbandaka acquired from sites across the UK between the years 2000 and 2010. RESULTS: We show that UK isolates of S. Mbandaka comprise of one clonal lineage which is adapted to proficient utilisation of metabolites found in soya beans under ambient conditions. We also show that this clonal lineage forms a biofilm at 25 °C, suggesting that this serovar maybe well adapted to survival ex vivo, growing in animal feed. Conversely, we show that S. Derby is made of two distinct lineages, L1 and L2. These lineages differ genotypically and phenotypically, being divided by the presence and absence of SPI-23 and the ability to more proficiently invade porcine jejunum derived cell line IPEC-J2. CONCLUSION: The results of this study lend support to the hypothesis that the differences in host ranges of S. Derby and S. Mbandaka are adaptations to pathogenesis, environmental persistence, as well as utilisation of metabolites abundant in their respective host environments. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-016-0628-4) contains supplementary material, which is available to authorized users.